The impact of a familiarization session on the magnitude and stability of active and passive pelvic floor muscle forces measured through intravaginal dynamometry. Issue 3 (12th March 2019) - Czyrnyj, Catriona S.; Bérubé, Marie‐Ève; Varette, Kevin; McLean, Linda
Abstract : Aims: The aim of this study was to investigate the impact of task familiarization on (1) the magnitude and (2) the repeatability of active and passive properties of the female pelvic floor muscles (PFMs) measured using automated intra‐vaginal dynamometry. Methods: Women attended three laboratory sessions at one‐week intervals. After receiving initial task instruction and feedback at the start of the first session, standardized instructions were given while women performed maximal effort voluntary contractions of their PFMs with the dynamometer arms open at two different diameters and kept their PFMs relaxed while the dynamometer arms opened to 40 mm at two speeds. Outcomes included baseline force, peak force, relative peak forces (N), rate of force development (N/s) and stiffness. Between session effects were tested for all outcomes using one‐way ANOVAs. Intra‐class correlation coefficients (ICCs) and minimal detectable change values were computed within each session and between sessions 1 and 2 and sessions 2 and 3. Results: Twenty nulliparous women (mean age = 35 ± 15 years) participated. No differences in the mean values were found across the three visits for any outcomes. Within sessions, neither ICC nor minimal detectable change differed among sessions and between‐session ICC values were not different between visits 1 and 2 and visits 2 and 3. Conclusions: There is no evidence of a familiarization effect over a two‐week period on the amplitude nor repeatability of dynamometric measures of active or passive PFM properties recorded from nulliparous women.